Una propuesta alternativa a la política monetaria - Rivas Santos, Pablo (2009)
While inflation processes in the world are moderate, inflation remained a concern. Inflation is associated with inappropriate increases in the money. These increases are politically motivated. Therefore, institutional elements are incorporated into the analysis of inflation. Among these elements are independent BCRS, which are perceived as an essential element in controlling inflation. But an independent BCR is not an institutional guarantee of zero or low inflation. If not for the excessive government interference in the monetary system, there would be no business cycle and no period of depression. Economic cycles are the result of mistakes made by deliberate government policies. The mistake is to create a monopoly where the money is controlled by the government. Since all banks create money side, which is redeemable in the monetary base, is a system that nobody can control. It is the government’s monopoly on the issuance of which is ultimately responsible. Inflation generates unemployment andalusia assign people to jobs that exist only because the demand for certain products go up temporarily, and those jobs disappear just stop increasing the amount of money. To avoid inflation, monetary policy must be conducted with the goal of maintaining stability in the value of money. Market forces can be adjusted to achieve that stability. We should put the issue of money in the hands of institutions whose business depends on its success in keeping the value of money they emit.